Human trafficking and Law No. 13.344/2016: legal-critical readings from the class, gender and race references (Revista do Tribunal Regional Federal da 3ª Região, 2019)
In these brief lines, we dare to question the limits of legislation that was "born to die" in its preventive and protective aspects. From a historical and dialectical materialist point of view, we could not analyze it in terms of the literal beauty of its words and intentions, but rather in terms of the confrontation between its protective abstractions and the reality of fiscal austerity and the dismantling of the Brazilian state in terms of guaranteeing social rights. As a dialectical reading of the concrete, we analyzed the extent to which the assistance-repression binary will become effective as a predominantly punitive policy, given that dependent assistance has an apparent facet par excellence, deepening a series of social contradictions in the face of the intrinsic selectivity of the penal system. We understand that public policies and the granting of social rights, although not revolutionary, are capable of creating barriers in this process, breaking cycles of violence, the precariousness of life and the vulnerability of subjects. Without this encouragement, what we have is a resurgence of the crisis (because the systemic logic of capital is not encouraged, but rather the permissiveness of human trafficking is increased) and barbarism (given the social and human impacts of the practice).
Keywords: trafficking in persons; law no. 13.344/2016; class/gender/race references; systemic contradictions; lack of effectiveness of public policies; growth of the penal face